Innovative monitoring mechanism: Evidence from rural drinking water sector in Nepal - Yadav, Maheshwar Prasad (Nepal Journal of Multidisciplinary Research, 2022)
The paper aims at determining innovative monitoring mechanism in the context of rural drinking water sector of Nepal. This study is based on both primary and secondary data. The necessary primary data were collected through telephone interview using semi-structured questionnaire while the secondary data were collected through database and publications. The collected data were analysed through simple statistical tools to derived results leading to major findings of the study. The study shows that the innovative monitoring mechanism such as, letter monitoring, hello monitoring, sensor monitoring, and toll-free monitoring are useful tools for efficient and effective monitoring of rural drinking water system in the context of developing countries like Nepal. Considering the innovative monitoring ladders and on-site monitoring, the study further concludes that a combination of two or more innovative monitoring mechanisms will make more sense for effective and efficient monitoring mechanism to keep the projects functional and sustainable. This study may be useful for development actor in the sector, academia, and policy makers. The study can be further extended by capturing learning from the implementation for these innovative monitoring mechanism in the context of rural and urban drinking water sector in Nepal.